Features of parking in megacities - Stepanov Mikhail; Skrininkova V.S. (E3S Web of Conferences, 2021)
The article deals with the issues of transport parking in megacities. Car parking has a huge impact on people and environment. The lack of parking spaces constrains economy and forces people to park incorrectly, which leads to traffic jams, undermines security and aesthetic appearance of urban spaces. The article discusses various parking options in megacities. The advantages and disadvantages of various parking options are shown. The main factors influencing the construction of parking lots in cities are considered, such as: construction and operating costs; type, location and use of the parking lot; availability and public transport possibilities; local vehicle ownership; a general need to reduce the use of high-emission vehicles. Foreign and domestic parking experience has been analyzed. The issues of the relation between the cost of parking, housing and the average net salary of residents are considered. Recommendations for the convenient design of parking lots are given. Dependences of the required number of parking lots for permanent and temporary parking of cars have been obtained.